2007
DOI: 10.1074/jbc.m702465200
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Catabolism of γ-Hydroxybutyrate in SH-SY5Y Human Neuroblastoma Cells

Abstract: ␥-Hydroxybutyrate (GHB) is an endogenous metabolite synthesized in the brain. There is strong evidence to suggest that GHB has an important role as a neurotransmitter or neuromodulator. The human aldo-keto reductase AKR7A2 has been proposed previously to catalyze the NADPH-dependent reduction of succinic semialdehyde (SSA) to GHB in human brain. In this study we have used RNA interference to evaluate the role of AKR7A2 in GHB biosynthesis in human neuroblastoma SH-SY5Y cells. Quantitative reverse transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 50 publications
1
29
0
1
Order By: Relevance
“…in Figure 1D, MYC induced not only ADHFE1 in HMEC-MYC cells but also the aldo-keto reductase AKR7A2, a key enzyme in the synthesis of 4-hydroxybutyrate in the brain (20). Additionally, ENCODE ChIP-seq data show that MYC has several binding sites in the AKR7A2 promoter region (Supplemental Figure 5).…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 94%
“…in Figure 1D, MYC induced not only ADHFE1 in HMEC-MYC cells but also the aldo-keto reductase AKR7A2, a key enzyme in the synthesis of 4-hydroxybutyrate in the brain (20). Additionally, ENCODE ChIP-seq data show that MYC has several binding sites in the AKR7A2 promoter region (Supplemental Figure 5).…”
Section: D-2hg Is the Predominant Enantiomer Elevated In Human Breastmentioning
confidence: 94%
“…In the present study, we identified (with at least 3 peptides) 23 proteins with significantly increased (Table 1) and 23 proteins with decreased ( Table 2) (1) - (Chihara et al, 2007), (2) - (Folci et al, 2014), (3) - (Chen et al, 2002), (4) - (Tanaka et al, 2000), (5) - (Ding and Shen, 2008), (6) - (Na et al, 2012), (7) - (Lyon et al, 2007), (8) - (Sweatt et al, 2004), (9) - (Bahn et al, 2002), (10) - (Manya et al, 1998), (11) - (Kamada et al, 2003), (12) - (McKenna et al, 2000), (13) - (Christel et al, 2012), (GO) -According to Gene Ontology database. …”
Section: Functional Clusters Of Altered Proteinsmentioning
confidence: 99%
“…The AKR7A2 and 1A1 enzymes are expressed in the brain and neuronal cells and thus could participate in SSA metabolism (Hoffman et al, 1980;Ireland et al, 1998). Recently, using siRNA, Lyon et al have demonstrated that in 2 human neuronal cell lines: neuroblastoma derived SH-SY5Y and astrocytoma 1321N1, AKR7A2 is responsible for over 80% of the SSA reductase activity (Lyon et al, 2007). Golgi localization of this enzyme has been speculated to facilitate the secretion of GHB (Kelly et al, 2002).…”
Section: E) Succinic Semialdehydementioning
confidence: 99%
“…The ubiquitously expressed AKR7A2 (human) and 7A4 (rat) enzymes have high affinity and catalytic efficiency for succinic semialdehyde (SSA), which is a metabolite of the neurotransmitter GABA. SSA is considered to be a physiological substrate of AKR7A2, which converts it to γ-hydroxybutyrate (GHB) and has been demonstrated to represent the major SSA reductase activity in cell lines of neuronal origin (Lyon et al, 2007). The second enzyme, AKR7A3, and its rat counterpart (AKR7A1) are significantly more efficient in reducing aflatoxin B 1 -dialdehyde (Guengerich et al, 2001).…”
Section: Akr7a2-a3 -Aflatoxin Reductasesmentioning
confidence: 99%
See 1 more Smart Citation